2004
DOI: 10.1117/12.580235
|View full text |Cite
|
Sign up to set email alerts
|

Status report on next-generation LADAR for driving unmanned ground vehicles

Abstract: The U.S. Department of Defense has initiated plans for the deployment of autonomous robotic vehicles in various tactical military operations starting in about seven years. Most of these missions will require the vehicles to drive autonomously over open terrain and on roads which may contain traffic, obstacles, military personnel as well as pedestrians. Unmanned Ground Vehicles (UGVs) must therefore be able to detect, recognize and track objects and terrain features in very cluttered environments. Although seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…To estimate the rotation matrix, a minimum of two non-parallel planar surfaces is required. It can be shown that equation (10) results in the least squares estimate of R.…”
Section: Attitude Change Estimationmentioning
confidence: 98%
See 1 more Smart Citation
“…To estimate the rotation matrix, a minimum of two non-parallel planar surfaces is required. It can be shown that equation (10) results in the least squares estimate of R.…”
Section: Attitude Change Estimationmentioning
confidence: 98%
“…For a comprehensive overview of Flash Ladar sensors the reader is referred to [9] [10]. Many early Flash Ladar sensors operate on the principle of measuring the phase difference (shift) between the transmitted and received (from the target) signal from a modulated light/laser.…”
Section: Introductionmentioning
confidence: 99%
“…Using these values for α and β, the thresholds T 2 and T 1 computed using the expressions in (14) are approximately 4 and −3, respectively.…”
Section: Track Maintenancementioning
confidence: 98%
“…The next generation of ladars will reduce this acquisition time by using scannerless focal plane array (FPA) [14]. Compared with RF, laser radiation is scattered by aerosols and cloud particles, which can limit its operating range.…”
Section: Introductionmentioning
confidence: 99%
“…The GDRS ladar has been described in Shneier et al (2003). Other imaging ladar technologies exist; several are described in Juberts and Barbera (2004).…”
Section: Imaging Ladar Technologymentioning
confidence: 99%